TOE AND HOOF DISEASES IN BREEDED CATTLE, ITS ETIOPATHOGENESIS AND CLINICAL SYMPTOMS (Conferencea, 2022)
Finger and hoof diseases of high productivity cattle brought to our country from foreign countries, its etiopathogenesis and clinical symptoms are discussed.